Hydrothermal Carbonisation Of Papaya Peels As Adsorbent For Removal Of Chloramphenicol Compounds - Teoh, Wei Xin (Universiti Sains Malaysia, 2022)
Chloramphenicol (CAP) is an active pharmaceutical ingredient (API) frequently detected in aquatic environments. As a result, continuous exposure to this antibiotic residue brings about adverse effects on human health and aquatic organisms. Recently, among several antibiotic removal technologies from water sources, adsorption method has gained the attention of researchers due to its simplicity in design, low preparation cost of activated carbon (AC) and high availability of feedstock from sustainable and renewable biomass waste. Locally, Malaysia’s fruit crop industry takes up the fourth largest land area for plantation purposes. Thus, in this study, the peel waste of papaya, one of Malaysia's most produced non-seasonal tropical fruits, was synthesised into papaya peel-derived activated carbon (PPAC) and tested for batch adsorption of CAP. In the synthesis of PPAC, hydrothermal carbonisation (HTC) was carried out followed by chemical activation via potassium hydroxide (KOH) and microwave heating to enhance its surface area, porosity and functional groups. Microwave power of activation process (364-700 W) and initial CAP concentration (5-100 mg/L) were investigated to study the PPAC adsorption capacity and percentage removal. Based on the experimental data, increased microwave power led to an increase in both adsorption capacity and percentage removal until an optimum value. Adsorption capacity also increased when initial CAP concentration increased owing to the higher driving force generated to overcome mass transfer resistance at higher initial CAP concentration. Maximum adsorption capacity of 22.9958 mg/g and maximum percentage removal of 82.40% were achieved. Moreover, the Langmuir isotherm model and pseudo-second-order kinetic model best fitted the data for CAP removal via PPAC. The findings indicated that PPAC was a promising and potential adsorbent in decontaminating CAP from water sources.